Electro-thermal transport in disordered nanostructures: a modeling perspective. Issue 7 (22nd June 2020) - Ducry, Fabian; Aeschlimann, Jan; Luisier, Mathieu
Abstract : We review here how molecular dynamics and quantum transport can be combined to shed light on the performance of, for example, conductive bridging random access memories, and we show that electro-thermal effects play a critical role. Abstract : Following the emergence of novel classes of atomic systems with amorphous active regions, device simulations had to rapidly evolve to devise strategies to account for the influence of disordered phases, defects, and interfaces into its core physical models. We review here how molecular dynamics and quantum transport can be combined to shed light on the performance of, for example, conductive bridging random access memories (CBRAM), a type of non-volatile memory. In particular, we show that electro-thermal effects play a critical role in such devices and therefore present a method based on density functional theory and the non-equilibrium Green's function formalism to accurately describe them. Three CBRAM configurations are investigated to illustrate the functionality of the proposed modeling approach.